2016
DOI: 10.1016/j.bios.2016.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed detection of lectins using integrated glycan-coated microring resonators

Abstract: We present the systematic design, fabrication, and characterization of a multiplexed label-free lab-on-a-chip biosensor using silicon nitride (SiN) microring resonators. Sensor design is addressed through a systematic approach that enables optimizing the sensor according to the specific noise characteristics of the setup. We find that an optimal 6 dB undercoupled resonator consumes 40% less power in our platform to achieve the same limit-of-detection as the conventional designs using critically coupled resonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…This value is higher than the predicted sensitivity from Equation 2, which is supposed to be caused by an underetching artifact of the waveguides that occurred during chip fabrication. Considering a random noise level of 0.05 pm, the theoretical detection limit (∆n at S/ N=3) for measuring changes in bulk refractive index is calculated to be about 2 × 10 -6 RIU, which is identical to the value reported by Ghasemi et al for SiN MRR resonators [16].…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…This value is higher than the predicted sensitivity from Equation 2, which is supposed to be caused by an underetching artifact of the waveguides that occurred during chip fabrication. Considering a random noise level of 0.05 pm, the theoretical detection limit (∆n at S/ N=3) for measuring changes in bulk refractive index is calculated to be about 2 × 10 -6 RIU, which is identical to the value reported by Ghasemi et al for SiN MRR resonators [16].…”
Section: Resultssupporting
confidence: 79%
“…In practice, a measurement rate of 10 Hz is used. This is very fast compared to measurement rates described for other systems such as once per 8 s (5 MRRs [16], or 32 MRRs [14]) or once per minute (12 MRRs [21]). This measurement rate is sufficient enough to monitor drastic changes in refractive index, for example, when regeneration is carried out with high salt solutions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghasemi et al reported five cascaded SiN microring‐based biosensors with site‐selective functionalization for multiplexed lection detection using a molecular printing system in 2016 (see Figure a,b). [ 133 ] Microrings functionalized with specific glycan for lectin binding suggests minimum non‐specific binding to other lectins. Figure 5c shows the real‐time binding curve of biotinylated Aleuria aurantia lectin (AAL) with a clear spectral redshift for two glycan‐coated microrings and only a weak response of the reference ring with a PEG coating.…”
Section: Silicon‐based Label‐free Optical Biosensorsmentioning
confidence: 99%